Influence of Process Parameters in a Cold Chamber under High Pressure Die Casting - Satendra Kumar Verma; Mr. Dinesh Dubey (International Journal of Scientific Research in Civil Engineering, 2025)
Die castings are among the most frequently produced mass-market goods in the metal working sector for complicated forms and Aluminium alloy that is lightweight. The needs of getting the light weight components with the same or improved mechanical, metallurgical properties, the industry is switching on these types of alloys. The present study is aimed at investigating the impact of various process parameters of cold chamber high pressure die casting machine on the cast product. Moreover the process parameters are further optimized with the aim to get optimum product quality. The various process parameters i.e. metal temperature (MP), 1st phase pressure, 2nd phase pressure and die open time were selected to study their impact on surface hardness (SH), surface roughness (SR), dimensional accuracy (DA) and porosity. The experiments were designed using Taguchi’s L9 orthogonal array because it provides the optimum results with the least number of set of experiments and the process parameters were optimized using desirability approach. In this paper, the models developed to predict Surface integrity [Surface Hardness (SH), Surface roughness (SR) and dimensional accuracy (DA)] showed significant effect of metal temperature and 2nd phase pressure whereas the 2nd phase pressure found only significant with respect to porosity response. The optimum process parameter levels were found at melting temperature of 589°C , 1st phase pressure 5 N/mm2 , 2nd phase pressure of 25 N/mm2 and die open time of 8 Second.